Kinerja Ibu Bekerja Milenial: Dampak Keseimbangan Kehidupan Kerja dan Kesehatan Mental dengan Dukungan Sosial dan Kepercayaan Organisasi sebagai Variabel Moderasi - Ni Luh Putu Ari Dharma Laksmi; Gede Sri Darma; Luh Putu Mahyuni (Jurnal Ilmu Sosial dan Humaniora, 2024)
The phenomenon of increasing suicide cases in Indonesia is attributed to mental health issues, with more women affected than men. Indonesian culture assigns women more significant roles and responsibilities in domestic and childcare duties, coupled with the pressure of modern work environments. This can cause several mental health problems for millennial working moms who juggle multiple roles. Achieving a healthy work-life balance is crucial for them. This study investigates the impact of work-life balance on millennial working moms' mental health and performance, focusing on the moderating effects of social support and organizational trust. Quantitative methods and SEM-PLS analysis collected data from 172 millennial working moms at the Directorate General of Taxes in Bali. The criteria for purposive sampling included being married, employed as permanent staff at the Directorate General of Taxes in Bali, and classified as millennials (born between 1980 and 2000). Findings reveal that work-life balance positively impacts mental health but does not directly influence performance. However, mental health mediates the relationship between work-life balance and performance. Social support and organizational trust did not significantly moderate these relationships. The study underscores the importance of maintaining a healthy work-life balance and mental health to enhance millennial working moms' performance while highlighting the need for organizational policies that foster trust and support work-life balance. Future research should incorporate qualitative methods to gain deeper insights into the personal experiences of millennial working moms.